Law Enforcement on Abuse of Building Use Rights in Waters and the Social Function of Public Spaces - Dina Sulistianingsih; Nia Kurniati Nia Kurniati; Betty Rubiati (Program magister Kenotariatan Fakultas Hukum Universitas Lambung Mangkurat, 2025)
The Ombudsman of the Republic of Indonesia highlighted the potentialmalpracticein issuing Building Use Rights Certificates in water areas. Issuing land rights certificates in water areas has the potential to violate the law. WALHI is investigating indications of affiliation between the companies that obtained the rights.certificateLand Rights with large property development corporations, which can lead to the privatization of marine space and threaten the sustainability of the ecosystem and the livelihoods of coastal communities, this problem is the background to this research.The purpose of this writing is to find answers and develop previous research regarding the granting of building use rights.his certificatedoes not correspond to the nature and purpose of granting rights in relation to the principle of the social function of public space;In this writing, the author uses a normative legal data analysis method, related to the issuance of building use rights certificates in the waters of Tangerang and Bekasi. This problem is thought to reflect an indicationmalpracticeadministrative matters. While land regulations in the UUPA and PP No. 18/2021 do not allow for the granting of land rights in waters, regulations in the maritime sector also explicitly address this. The Ministry of Maritime Affairs and Fisheries asserts that the establishment of building use rights in these waters is unlawful and disrupts the activities of thousands of fishermen. The issuance of land title certificates in these waters has raised indications of Mal practice Administration.